Cryptolepine-Induced Cell Death of Leishmania donovani Promastigotes Is Augmented by Inhibition of Autophagy - Sengupta, Souvik (SAGE-Hindawi Access to Research, 2011)
Leishmania donovani are the causative agents of visceral leishmaniasis worldwide. Lack of vaccines and emergence of drug resistance warrants the need for improved drug therapy and newer therapeutic intervention strategies against leishmaniasis. In the present study, we have investigated the effect of the natural indoloquinoline alkaloid cryptolepine on L. donovani AG83 promastigotes. Our results show that cryptolepine induces cellular dysfunction in L. donovani promastigotes, which leads to the death of this unicellular parasite. Interestingly, our study suggest that cryptolepine-induced cell death of L. donovani is counteracted by initial autophagic features elicited by the cells. For the first time, we show that autophagy serves as a survival mechanism in response to cryptolepine treatment in L. donovani promastigotes and inhibition of autophagy causes an early increase in the amount of cell death. This study can be exploited for designing better drugs and better therapeutic strategies against leishmaniasis in future.